1990
DOI: 10.1002/eji.1830200534
|View full text |Cite
|
Sign up to set email alerts
|

Primary responses of human T cells to mycobacteria: a frequent set of γ/δ T cells are stimulated by protease‐resistant ligands

Abstract: T lymphocyte subsets expressing either T cell receptor alpha/beta or gamma/delta were selected from human peripheral blood T cells and proliferative responses to molecular mass-fractionated mycobacterial lysates were determined. alpha/beta T cells primarily responded to fractions greater than 30 kDa whereas gamma/delta T cells preferentially reacted to fractions less than 3 kDa. Protease digestion abolished the stimulating activities for alpha/beta T cells, confirming that alpha/beta T cells respond to protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(133 citation statements)
references
References 20 publications
6
126
1
Order By: Relevance
“…For example, there have been conflicting reports of numbers of circulating TCR 7^ĉ ells in patients with tuberculosis [37,38]. Furthermore, in vitro tests have shown that TCR 7^^ cells do not respond equally to all tnycobacterial preparations [30] and usually do not respond to PPD preparations (K. PfelTer, personal communication). Indeed, one group has shown that TCR 76^ cells respond to live Myco.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there have been conflicting reports of numbers of circulating TCR 7^ĉ ells in patients with tuberculosis [37,38]. Furthermore, in vitro tests have shown that TCR 7^^ cells do not respond equally to all tnycobacterial preparations [30] and usually do not respond to PPD preparations (K. PfelTer, personal communication). Indeed, one group has shown that TCR 76^ cells respond to live Myco.…”
Section: Discussionmentioning
confidence: 99%
“…is increased in CD compared with UC and non-inllammatory bowel disease controls. A secondary aim was to examine the responses of T cell subsets and the minority T cell population expressing the "rM heterodimer of the T cell antigen receptor (TCR), as TCR 71^' ' cells have been implicated in 'first line" immune defences against mycobacteria [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although the function of ␥␦ T cells is not quite clear yet, there is accumulating evidence of their importance in response to intracellular microorganisms such as Mycobacterium tuberculosis or Listeria monocytogenes [22][23][24] and anti-leukemia effects. 25 In addition, it is now clear that ␥␦ T cells can recognize nonpeptide antigens [26][27][28] in a manner which is entirely different from how ␣␤ T cells recognize their processed antigens in the context of major histocompatibility complex (MHC)/peptide. 29,30 Our results showed that recovery of CDR3 complexity of the TCR-␦ chain appeared to be almost complete during the initial 2 months after transplantation, suggesting that marrow transplant recipients are immunocompetent for the microorganisms with antigens that ␥␦ T cells can recognize.…”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66]98 However, while many murine cells were found to react with mycobacterial PPD and HSP-65, 66 human mycobacteriareactive cd T cells failed to react with PPD and HSP-65. 99 Searching for alternative Ags, Pfeffer and colleagues 100 found that most human mycobacteria-reactive cd T cells responded to Ags contained in fractions of mycobacterial lysates with a molecular mass of ,3 kDa. Moreover, these Ags were protease-resistant.…”
Section: Non-peptidic Agsmentioning
confidence: 99%